Representasi Ketidakadilan Gender dalam Film Please Be Quiet: Analisis Wacana Kritis Sara Mills - Khoirunnisa, Nadia; Hambali, Muhammad (Universitas Muhammadiyah Surabaya, 2025)
Women are often one of the victims marginalized by the upper class. Television reports, novels, and movie stories often portray women in positions they shouldn't have occupied. The purpose of this study is to examine the role of female characters in the film Be Quiet using a critical discourse analysis approach based on the theoretical framework developed by Sarah Mills. This study uses a descriptive approach in a qualitative method. The data collection technique in this study is the data transcription technique. The transcription data technique in this study was carried out by watching a short film titled Please Be Quiet on the Youtube channel repeatedly, recording all dialogues, and selecting data based on the focus of the research. The data of this research is divided into two categories, namely primary data and secondary data. Primary data in the form of text from film transcripts containing dialogues from the characters Putri, Sarah and Pak Benny; While secondary data is in the form of visual symbols contained in the film. Primary data were analyzed using Sara Mills' discourse analysis theory; while secondary data were analyzed using Charles Sanders Peirce's semiotic theory. The results of the study show that in the film Please Be Quiet, women are sexually harassed, threatened, and injustice experienced by figures from superiors, underlining the existence of systematic power inequality in the workplace.